Stratigraphy and Sedimentology of Coastal Lacustrine Basins, Northeastern Ellesmere Island, N. W. T. - Retelle, Michael (Géographie physique et Quaternaire, 1986)
ABSTRACTSediment cores recovered from three high arctic coastal lake basins contain a sequence of glaciomarine sediments overlain by laminated to massive-bedded lacustrine sediments. Glaciomarine sediments were deposited while the basins were isostatically depressed below sea level. Subsequent to emergence of the basin from the sea, lacustrine sediments accumulated in each basin. A transitional fades between the marine and lacustrine units represents an isolation interval during which trapped sea water lay beneath a freshwater lens. Sedimentological and faunal evidence from sediment cores demonstrates that embayments were closed and fluvial sedimentation was minimal during the glacial maximum (ca. 8000-8200 BP) Subsequent increases in sand content and macrofaunal abundance reflects increases in mobility of sea ice and fluvial input during the middle Holocene. Late HoIocene cooling trends are demonstrated by decreases in ice rafted material and an increase in diffuse bedding in lake surface sediments.